Estimated size of the clinical medical imaging physics workforce in the United States. Issue 7 (14th June 2022) - Rose, Sean D.; Jordan, David W.; Bevins, Nicholas B.; Dave, Jaydev K.; Hintenlang, David E.; Lofton, Brad K.; Patel, Pankaj
Abstract: There is no current authoritative accounting of the number of clinical imaging physicists practicing in the United States. Information about the workforce is needed to inform future efforts to secure training pathways and opportunities. In this study, the AAPM Diagnostic Demand and Supply Projection Working Group collected lists of medical physicists from several state registration and licensure programs and the Conference of Radiation Control Program Directors (CRCPD) registry. By cross‐referencing individuals among these lists, we were able to estimate the current imaging physics workforce in the United States by extrapolating based on population. The imaging physics workforce in the United States in 2019 consisted of approximately 1794 physicists supporting diagnostic X‐ray (1073 board‐certified) and 934 physicists supporting nuclear medicine (460 board‐certified), with a number of individuals practicing in both subfields. There were an estimated 235 physicists supporting nuclear medicine exclusively (150 board‐certified). The estimated total workforce, accounting for overlap, was 2029 medical physicists. These estimates are in approximate agreement with other published studies of segments of the workforce.